SANKSI DALAM PERSPEKTIF FIKIH, PENDIDIKAN DAN PSIKOLOGI (IAIN Tulungagung, 2022)
This study examines sanctions from the perspective of fiqh, education and psychology. The problem is that not all sanctions can have a deterrent effect on perpetrators of crime, and some perpetrators of criminal acts repeat the mistakes they have made. On the other hand, sanctions are seen as a form of retaliation for crimes committed. From these problems, the question arises of how to integratively review both the fiqh, educational, and psychological perspectives on sanctions. This research is a library research. Research materials were obtained through books and journals related to sanctions from a fiqh, educational and psychological perspective. After the collected data is processed by reviewing the existing materials based on the discussion studied and analyzed in a descriptive way. The results of the study found that in the perspective of fiqh there are three kinds of sanctions, namely qisas, hudud and ta'zir. According to an educational perspective, the imposition of sanctions is adjusted to the severity of the violation so that the perpetrator does not repeat the same action. Meanwhile, from a psychological perspective, prior to imposing sanctions, it is necessary to first seek clarification on the psychological condition of the perpetrator, victim and witness so that law enforcement officials can make the right decision.